1979
DOI: 10.1136/jcp.32.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic organisms in postoperative wounds.

Abstract: SUMMARY A survey of the bacteria found in postoperative wounds was undertaken during a 14-month period. The yields of aerobic and anaerobic bacteria in 65 appendicectomy wounds were compared; 42 wounds yielded aerobes and 51 anaerobes. Seventy-eight other operation wounds yielded anaerobes, and, overall, 33 wounds yielded anaerobes only. Bacteroides sp were the most common anaerobic organisms isolated from all operation sites except the lung.The examination of infected postoperative wounds for bacteria permits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…aureus, E. coli, and C. albicans were chosen to test the process of homogenization on important representatives of Gram-positive and Gram-negative bacteria as well as on yeasts, since microbiological analyses from surgical wound and soft tissue infections, abscesses, or intraabdominal infections often reveal a polymicrobial etiology (Brook, 1989a(Brook, , 1989bBrook and Randolph, 1981;Pathare et al, 1998;Sanderson et al, 1979;Summanen et al, 1995). Inoculation doses of either 2 × 10 2 or 1.2 × 10 3 CFU were administered to achieve well countable numbers when directly streaking the inoculated tissues over the plates.…”
Section: Discussionmentioning
confidence: 99%
“…aureus, E. coli, and C. albicans were chosen to test the process of homogenization on important representatives of Gram-positive and Gram-negative bacteria as well as on yeasts, since microbiological analyses from surgical wound and soft tissue infections, abscesses, or intraabdominal infections often reveal a polymicrobial etiology (Brook, 1989a(Brook, , 1989bBrook and Randolph, 1981;Pathare et al, 1998;Sanderson et al, 1979;Summanen et al, 1995). Inoculation doses of either 2 × 10 2 or 1.2 × 10 3 CFU were administered to achieve well countable numbers when directly streaking the inoculated tissues over the plates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to have been isolated from a range of skin infections including chronic wounds (Bowler & Davies, 1999b), leg ulcers (Bowler & Davies, 1999a), nonpuerperal breast infection (Edmiston et al, 1990), burn wound infections (Mousa, 1997), acute (surgical) wounds (Sanderson et al, 1979) and diabetic foot infections (Wheat et al, 1986). It has been reported to have been isolated from a range of skin infections including chronic wounds (Bowler & Davies, 1999b), leg ulcers (Bowler & Davies, 1999a), nonpuerperal breast infection (Edmiston et al, 1990), burn wound infections (Mousa, 1997), acute (surgical) wounds (Sanderson et al, 1979) and diabetic foot infections (Wheat et al, 1986).…”
Section: Clinical Importancementioning
confidence: 99%
“…With the exception of clean operative procedures, surgical wound infections are recognized as having a polymicrobial etiology, involving both aerobic and anaerobic microorganisms (Table 3) (2,35,36,38,64,175,212), and intra-abdominal infections normally reflect the microflora of the resected organ (34,175). Reported wound infection rates following orthopedic surgery are relatively low (2 to 6.8%) (20,61,223), and similar studies, involving a large number of generalized postoperative wound types, have reported overall infection rates of 3.4% in 5,129 operations (1), 4.7% in 62,939 operations (57), and 9.4% in 1,770 operations (238).…”
Section: Wound Infectionmentioning
confidence: 99%